cHCC‐CCA: Consensus terminology for primary liver carcinomas with both hepatocytic and cholangiocytic differentation - Brunt, Elizabeth; Aishima, Shinichi; Clavien, Pierre‐Alain; Fowler, Kathryn; Goodman, Zachary; Gores, Gregory; Gouw, Annette; Kagen, Alex; Klimstra, David; Komuta, Mina; Kondo, Fukuo; Miksad, Rebecca; et al. (Hepatology (Baltimore, Md.), 2018)
Primary liver carcinomas with both hepatocytic and cholangiocytic differentiation have been referred to as “combined (or mixed) hepatocellular‐cholangiocarcinoma.” These tumors, although described over 100 years ago, have attracted greater attention recently because of interest in possible stem cell origin and perhaps because of greater frequency and clinical recognition. Currently, because of a lack of common terminology in the literature, effective treatment and predictable outcome data have been challenging to accrue. This article represents a consensus document from an international community of pathologists, radiologists, and clinicians who have studied and reported on these tumors and recommends a working terminology for diagnostic and research approaches for further study and evaluation. Conclusion: It is recommended that diagnosis is based on routine histopathology with hematoxylin and eosin (H&E); immunostains are supportive, but not essential for diagnosis. (Hepatology 2018;68:113‐126).